IMPROVING THE STUDENTS’ ENGLISH LEARNING OUTCOMES THROUGH TEAM GAME TOURNAMENT MODEL IN ENGLISH FOR ISLAMIC EDUCATION COURSE - Haryanto, Haryanto (Center of Language and Cultural Studies [CLCS], 2023)
This research aims to increase the students’ ability of semester 2 of Islamic Education Study Program in English course through the learning model of Team Game Tournament (TGT). The subjects of this classroom action research were second-semester students of the Islamic Religious Education study program. The variables of this study consist of student scores and lecturer activity variables. The student variables were taken from the ability to solve English questions and student activities in class. The results of the study showed that the performance of the lecturers following the criteria on the indicators, this was shown from the results of observations in the first cycle and the second cycle was good. This means that the lecturer's performance in learning has increased. Student activity is following the indicators, this is shown from student activity in cycle I with a percentage of 66.67% and cycle II with a processing rate of 93.33%, this means that student activity during learning is very good. Student learning outcomes are following the criteria on the indicators, as indicated by the average student evaluation results in cycle I was 6.88, and cycle II was 8.62. In cycle, I, 17 students, or 47.22% completed their studies and 19 students or 52.78% did not complete them, and 47.22% classical learning completeness. In cycle II, 36 students completed their studies and there were no students who did not complete their studies, and the classical learning mastery was 100.00%. This means that the evaluation results of cycle II are better (increase) than cycle I and do not need to be continued in the next cycle. In addition, the student's response to the implementation of the learning model of Team Game Tournament (TGT) was relatively high, that reached 81.25%.